Magnetic resonance imaging of the Achilles tendon using ultrashort TE (UTE) pulse sequences. - Robson, M; Benjamin, M; Gishen, P; Bydder, G (2004)
AIM: To assess the potential value of imaging the Achilles tendon with ultrashort echo time (UTE) pulse sequences. MATERIALS AND METHODS: Four normal controls and four patients with chronic Achilles tendinopathy were examined in the sagittal and transverse planes. Three of the patients were examined before and after intravenous gadodiamide. RESULTS: The fascicular pattern was clearly demonstrated within the tendon and detail of the three distinct fibrocartilaginous components of an "enthesis organ" was well seen. T2* measurements showed two short T2* components. Increase in long T2 components with reduction in short T2 components was seen in tendinopathy. Contrast enhancement was much more extensive than with conventional sequences in two cases of tendinopathy but in a third case, there was a region of reduced enhancement. CONCLUSION: UTE pulse sequences provide anatomical detail not apparent with conventional sequences, demonstrate differences in T2* and show patterns of both increased and decreased enhancement in tendinopathy.